Critical Reading Skills Analysis Among Seventh-Grade Students at SMP Negeri 5 Padangsidimpuan - Harianja, Rizki Wulandari; Tambunan, Elissa Evawani; Ramadhani, Yulia Rizki; Tambunan, Mahrani (ETANIC Journal Of English Language Teaching And Applied Linguistics, 2025)
This study examines the critical reading skills of seventh-grade students at SMP N 5 Padangsidimpuan. Using a quantitative descriptive approach, the research assessed 30 students through a critical reading test based on Nurhadi's six aspects of critical reading: remembering explicit facts, interpreting implied meanings, applying concepts, analyzing content, synthesizing content, and evaluating reading material. Results indicate that students demonstrate very good abilities in five aspects, with scores ranging from 80 to 100, particularly excelling in remembering explicit facts (scores of 97-100) and evaluating content (scores of 90-97). However, synthesizing reading content emerged as an area needing improvement, with scores of 70 and 57. The overall average score of 85 places students' critical reading abilities in the "Very Good" category according to Arikunto's rating scale. These findings suggest that while students have developed strong foundations in most aspects of critical reading, targeted instruction in synthesizing information would benefit their comprehensive critical reading development. The study recommends implementing diverse reading materials, collaborative learning activities, and cross-curricular integration of critical reading skills to enhance students' abilities, particularly in synthesizing textual information.